Water level detector / Mohd. Johanif Mohamed Nadzirin and Affendy Mohamad Nor - Mohamed Nadzirin, Mohd. Johanif; Mohamad Nor, Affendy (2001)
As we know, water contains free moving ions such as +H and -OH, So, when the sensor touches water, the +H will move to the negative terminal and the -OH ion will go to the positive terminal at the sensor. This kind of movement thus, making it eligible for the circuit to operates as it is built to be. The result are 3 in 1 output that are sound from the speaker that you can hear, running light from the LED that you can see and rotational movement from the motor that you can feel.